Brexit decision is likely to reduce growth in the short term - Ferdinand Fichtner; Christoph Große Steffen; Michael Hachula; Thore Schlaak (DIW Economic Bulletin, 2016)
The high degree of uncertainty about the United Kingdom's (UK) economic future following the June 23 Brexit referendum is leading to a flight into safe assets, and will most likely worsen financing conditions for British companies. In addition, companies could reduce investment and postpone hiring decisions. This is likely to start dampening economic growth in the UK in the short term, thus reducing the export possibilities for the euro area and Germany. The German automotive industry, which counts the UK as a major export destination, will be the most affected; German producers of wood, paper, and leather goods, as well as those of pharmaceu-ticals and chemical products, will also feel the impact. Assuming that the Brexit decision reduces British imports by 12.5 percent by the end of next year compared to a Remain-vote scenario, Germany's economic growth in 2017 could be half a percentage point lower than previously expected.
Keywords: E32; E65; E66; 330; Brexit; economic uncertainty; trade channel